Rios urbanos de Manaus: proposta teórico-metodológica para gestão e regulação de recursos hídricos com base no igarapé do quarenta - Martins Júnior, Delcio Fernando (2018)
The urban rivers became altered and degraded spaces, due to the intense urbanization of their banks, where these water bodies started to have a waste disposal function, with the population of the cities turning their backs on them. This trend has also been notable in the brazilian rivers and in the “igarapés” of the city of Manaus, being necessary the proposal of alternatives aiming the change of this diagnosis. The analysis of the urban rivers of the city of Manaus was carried out with the purpose of proposing measures for the participative management of the waters, according to the National Policy of Water Resources. Through a study of the relevant legislation, bibliographical review through papers, dissertations, thesis and books, and access to public agencies data, through the use of exploratory, explanatory and empirical methodologies, we sought to know the historical processes that led urban rivers to the present condition, as well as a state of the art of several projects and plans that sought to revitalize urban rivers in various parts of the world. In the case of the study cutout the city of Manaus, we sought knowledge of the process of occupation of the city from its “igarapés’ and the history of alterations and losses of functions performed in these environments, associated with the inefficiency of basic sanitation policies and the not achieving the objectives of PROSAMIM. It was also observed the use of the soil of the Quarenta basin and the banks of the Igarapé do Quarenta, and the most diverse types of occupations were identified, aiming at a simplified framework of waters of the basin. From the change of the mentality of the society-environment relationship, it was observed that the urban regeneration projects are currently seeking not only to recover water quality, but to integrate the rivers with the city's landscape, by means of a valorization ecological and aesthetic, recreating a relationship of the river with the population, a relationship that was forgotten, a procedure that was not carried out through PROSAMIM, which focused on improving the quality of the dwellings that are located on the banks of “igarapés” of the city of Manaus. On the banks of the Igarapé do Quarenta, an intense urbanization was observed, with different types of occupations exerting pressure on the water body, altering the quality and quantity of the waters. Environmental policies and water resources management in the region of the Qaarenta basin were also observed, with areas of permanent preservation occupied and the release of solid and liquid wastes in the bed of streams. In relation to the water quality of the Quarenta and its tributaries, a framing proposal was made where the “igarapés” of the headwaters of the basin and their springs received special classification, those that cross the Industrial Pole, class 2, with the most impacted water bodies with presence of the Urban occupation receiving classification 4. The suggested measures aimed at the requalification of the Igarapé do Forty are based on the revaluation of this water body and on the residents' awareness of the importance of this stream, being transversal and involving public power and civil society, in the management and implementation of new plans and existing policies.